2021
DOI: 10.31926/but.shk.2021.14.63.2.19
|View full text |Cite
|
Sign up to set email alerts
|

The Dimension of Motivation in Practicing Sports in Adults with Locomotor Disability

Abstract: For the current research, the focus is on adults with locomotor disabilities, adults that practice a certain sporting activity, having as objective undergoing a sociological research regarding the role of motivation in the sporting activity and the reasons for which adults with disabilities practice a sport in the first place. The research has been done on a number of 30 people with diverse disabilities and as a research method one has used a questionnaire that identifies the role of motivation in practicing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The fact that athletes with physical disabilities love competition and have the desire to achieve goals positively affects their motivation to participate in sports ( McLoughlin et al, 2017 ). It is stated that the motivation of individuals with physical disabilities to participate in physical activity is influenced by the desire to achieve performance, the desire to succeed, and the spirit of competition ( Mindrescu, 2022 ). In this direction, it can be concluded that the participants have a personality trait compatible with wheelchair basketball sport.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that athletes with physical disabilities love competition and have the desire to achieve goals positively affects their motivation to participate in sports ( McLoughlin et al, 2017 ). It is stated that the motivation of individuals with physical disabilities to participate in physical activity is influenced by the desire to achieve performance, the desire to succeed, and the spirit of competition ( Mindrescu, 2022 ). In this direction, it can be concluded that the participants have a personality trait compatible with wheelchair basketball sport.…”
Section: Discussionmentioning
confidence: 99%